Characterization and ecological significance of a seed bank from the Upper Pennsylvanian Wise Formation, southwest Virginia - PETRA S. YEHNJONG; MICHAEL S. ZAVADA; CHRIS LIU (Acta Palaeobotanica)
Soil seed banks are important to the maintenance and restoration of floras. Extant seed banks exhibit unique characteristics with regard to the distribution of seed size and seed density. Seeds were recovered from the Upper Pennsylvanian Wise Formation in southwest Virginia. Structurally preserved seeds were also examined from coal balls of the Pennsylvanian Pottsville and Allegheny Groups, Ohio. The size distribution of the seeds from the Wise Formation is similar to that of structurally preserved seeds of the Upper Pennsylvanian Pottsville and Allegheny Group coal balls. In contrast, the seed size distributions in extant wetland, grassland, woodland and forest habitats are significantly narrower than that of seeds from the Pennsylvanian seed banks. Larger seeds are less dependent on light for germination, and aid in seedling establishment more than smaller seeds, especially in dense stable forests where disturbance events are rare. Large seed size may contribute to increased seed longevity, which reduces the effect of environmental variability on seed germination and development. The significantly larger size of the Palaeozoic seeds may have imparted an advantage for seedling establishment in the dense Palaeozoic forests. The preponderance of large seeds may be a result of the absence of large seed predators (e.g. herbivorous tetrapods), and may have been an evolutionary strategy to minimize damage to the embryo from a predator population dominated by small invertebrates with chewing or sucking mouthparts. The estimated seed density of 192 seeds/m2 in the Palaeozoic seed bank falls within the range of modern seed banks, but at the lower end of modern seed bank densities in a variety of habitats.